2011
DOI: 10.1103/physrevd.84.055020
|View full text |Cite
|
Sign up to set email alerts
|

UsingMT2to distinguish dark matter stabilization symmetries

Abstract: We examine the potential of using colliders to distinguish models with parity (Z 2 ) stabilized dark matter (DM) from models in which the DM is stabilized by other symmetries, taking the latter to be a Z 3 symmetry for illustration. The key observation is that a heavier mother particle charged under a Z 3 stabilization symmetry can decay into one or two DM particles along with Standard Model (SM) particles. This can be contrasted with the decay of a mother particle charged under a parity symmetry; typically, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 90 publications
1
49
0
Order By: Relevance
“…For example, it has been shown that DDM ensembles can give rise to statistically significant deviations from the kinematic distributions associated with traditional, single-particle dark-matter candidates at colliders [6], at direct-detection experiments [7], and at cosmicray detectors [8]. Similar analyses have also been performed for other non-minimal dark-matter scenarios in the context of direct detection [4], indirect detection [9], and collider searches [10][11][12]. However, in general, it is also important to investigate the effects of correlations between kinematic variables and their impact on distribution shapes.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, it has been shown that DDM ensembles can give rise to statistically significant deviations from the kinematic distributions associated with traditional, single-particle dark-matter candidates at colliders [6], at direct-detection experiments [7], and at cosmicray detectors [8]. Similar analyses have also been performed for other non-minimal dark-matter scenarios in the context of direct detection [4], indirect detection [9], and collider searches [10][11][12]. However, in general, it is also important to investigate the effects of correlations between kinematic variables and their impact on distribution shapes.…”
Section: Introductionmentioning
confidence: 64%
“…For example, the shapes of the M T 2 distributions associated with DDM ensembles with larger values of γ peak at lower values of M T 2 while still retaining a significant tail which extends out to the kinematic endpoint at M max T 2 = m φ . For large ∆m, the individual contributions to the distributions from events with different values of m a and m b can be independently resolved, as shown in the right panel of the figure, and a "kink" behavior arises similar to that which arises in the case in which multiple invisible particles are produced from a single decay chain [11]. By contrast, for small ∆m, these contributions cannot be resolved, and the tail of the resulting distribution appears smooth.…”
Section: Kinematic Distributionsmentioning
confidence: 83%
“…Of course, in cases in which only a small number of the χ n are kinematically accessible in ψ decays, these invariant-mass distributions are distinguished by the presence of multiple kinematic edges. Note that similar features arise in other contexts as well, most notably that in which a parent particle can decay into final states involving different multiplicities of the same stable dark-matter particle [5,6]. By contrast, in cases in which the number of kinematically-accessible χ n is large and the decay phenomenology of the ψ particles depends more sensitively on the full structure of the DDM ensemble, qualitatively different features emerge.…”
Section: Dynamical Dark Matter At the Lhc: General Considerationsmentioning
confidence: 83%
“…Shape of the visible invariant mass can effectively carry informations on topology along with the mass spectrum [9] of the decay chain. Underlying DM stabilising symmetry can also be probed [10][11][12] using kinematic edge and cusp in the invariant mass distributions and from the shapes of transverse mass variable M T 2 . Even the assumption of one particular underlying symmetry allows some fixed number of different topologies from which the correct one can be identified comparing suitable kinematic variables [13].…”
Section: Jhep03(2015)142mentioning
confidence: 99%